Exploration of a simplified clinical examination for scabies to support public health decision-making. - Michael Marks; Daniel Engelman; Lucia Romani; Daniel Mason; Oliver Sokana; Mike Kama; Margot Whitfeld; Andrew C Steer; John Kaldor (Public Library of Science (PLoS), 2018)
Introduction In most settings, the diagnosis of scabies is reliant on time-consuming and potentially intrusive clinical examination of all accesible regions of skin. With the recent recognition of scabies as a neglected tropical disease by the World Health Organization there is a need for standardised approaches to disease mapping to define populations likely to benefit from intervention, and to measure the impact of interventions. Development and validation of simplified approaches to diagnose scabies would facilitate these efforts. Methods We utilised data from three population-based surveys of scabies. We classified each individual as having scabies absent or present overall, based on whole body assessment, and in each of 9 regions of the body. We calculated the sensitivity of diagnosing the presence of scabies based on each individual body region compared to the reference standard based on whole body examination and identified combinations of regions which provided greater than 90% sensitivity. We assessed the sensitivity according to gender, age group, severity of scabies and the presence or absence of impetigo. Results We included 1,373 individuals with scabies. The body regions with highest yield were the hands (sensitivity compared to whole body examination 51.2%), feet (49.7%), and lower legs (48.3%). Examination of the exposed components of both limbs provided a sensitivity of 93.2% (95% CI 91.2-94.4%). The sensitivity of this more limited examination was greater than 90% regardless of scabies severity or the presence or absence of secondary impetigo. Discussion We found that examination limited to hands, feet and lower legs was close to 90% for detecting scabies compared to a full body examination. A simplified and less intrusive diagnostic process for scabies will allow expansion of mapping and improved decision-making about public health interventions. Further studies in other settings are needed to prospectively validate this simplified approach.